Perancangan Model Ontologi pada Sistem Pencarian Informasi Proposal Tugas Akhir Berbasis Web Semantik - Trisnajayanti, Anak Agung Sinta; Suputra, I Putu Gede Hendra (Jurnal Nasional Teknologi Informasi dan Aplikasnya, 2022)
The obligation of a student to graduate at the Strata-1 (S1) level is to complete a thesis. The thesis research process begins with the preparation of the final project proposal. In the Informatics Study Program, Udayana University students do not have a place to see references from previous student final project proposals. In the library there is only a thesis, where the format of the thesis and the final project proposal has a difference. Therefore, a system was created to search for information on student proposals from the Udayana University Informatics Study Program. The system is made based on the semantic web and to support the semantic web in this research an ontology model is made in the domain of the Final Project Proposal. The method used in making the ontology model is Methontology. The ontology design is made using Protégé and queries using SPARQL. This design produces 5 classes, 7 object properties, 11 data properties, and 57 individuals. Evaluation using SPARQL by asking questions and the results are as desired.